A comparison of saliency based sensorless control techniques for a PM machine - Duan, Yu (2012)
This thesis analyzes saliency-based sensorless control methods for AC surface mounted permanent magnet machines (PMSM), because PMSMs have features that make them attractive for use in industrial drives: small size, high efficiency, low maintenance, high dynamics, and high power density. The thesis focuses on four different HF injection sensorless methods, which utilize resistance and inductance based saliencies for position estimation: the measurement axis method, the eddy current resistance based saliency tracking method, the eddy current inductance based saliency tracking method, and the PWM switching frequency injection method. The emphasis is in the comparison of the four HF saliency tracking methods under various conditions such as steady state, load impact, speed reversal, and zero and low speed operation. The amplitude and frequency of the injection signals are also compared to choose the best HF injection signal for the four saliency tracking methods. The best sensorless control method using eddy current resistance based saliency is introduced and the experimental results confirm the expected advantages for this sensorless application.